OP0330 FRA2 overexpression leads to systemic autoimmunity by decreasing IL-2 responsiveness and thymic treg development. (15th June 2017) - Renoux, F; Stellato, M; Impellizzieri, D; Vogetseder, A; Huang, R; Subramaniam, A; Dees, C; Distler, JHW; Kania, G; Boyman, O; Distler, O
Abstract : Background: Fos-related antigen 2 (Fra2) is a transcription factor belonging to the Fos family proteins which is part of the AP-1 transcription complex. We recently described a Fra2 transgenic (tg) mouse model which develops a multi-organ inflammatory phenotype affecting skin, lungs, thymus, liver and salivary glands. We have observed abnormalities in the T cell compartment, particularly in regulatory T (Treg) cells, which led us to hypothesize that Fra2 tg mice develop a T cell driven autoimmune phenotype. Objectives: To demonstrate the autoimmune phenotype of Fra2 tg mice and to characterize the mechanisms leading to Treg cell abnormality. Methods: We used previously generated Fra2 tg overexpressing mice. T lymphocyte populations were analyzed by flow cytometry for expression of activation markers and secretion of cytokines. We transferred purified CD4+ T cells into Rag2-/- mice lacking T and B cells, and we generated Rag2-/-Fra2 tg mice. Bone marrow cells were transferred into lethally irradiated recipients to create Fra2-WT bone marrow chimeric mice. Results: Fra2 tg mice backcrossed onto a Rag2 -/- background did not develop inflammatory manifestations (n=6), demonstrating the dependence on T and/or B cells of the autoimmune phenotype. In line with this, the transfer of purified CD4 + cells from 16 week-old Fra2 tg mice into Rag2 -/- recipients was sufficient to transfer the disease phenotype (n=3). Analysis of T cell populations from Fra2 tg mice showed the presence of activated CD4 + and CD8 + cells in the spleen and lungs. After in vitro stimulation, we found that CD4 + T cells from Fra2 tg mice produced the Th2 cytokines IL-4, IL-5 and IL-13. Thus, these data strongly suggest a T cell-driven autoimmune disease in these mice. We previously reported a striking decrease of Treg cells in Fra2 tg mice, which might explain the autoimmune phenotype observed. Supporting this idea, we found that 3 week-old mice were devoid of organ manifestations and of T cell activation, but presented the same defect in the Treg cell population (n=6, p<0.001). Analysis of thymuses from these young tg mice showed an abnormal development of thymic Treg (tTreg) cells. In particular, we could observe a normal population of tTreg precursors (CD4 + CD8 - CD25 + FoxP3 - ), but a strong decrease in mature tTreg cells (CD4 + CD8 - CD25 + FoxP3 +, n=4), suggesting a perturbation in the transition from tTreg precursors to mature tTreg cells in Fra2 tg mice. We also found that in vivo stimulation with IL-2 failed to induce the proliferation of Treg cells in Fra2 tg mice compared to WT mice, suggesting that Fra2 overexpression affects IL-2 sensitivity of T cells. Finally, Fra2-WT bone marrow chimera mice also displayed a decreased percentage of Tregs confirming a cell-intrinsic and hematopoietic role of Fra2 in Treg cell development. Conclusions: Our data suggest that Fra2 controls tTreg cell development, possibly by modulating IL-2 signaling in T cells, which leads to autoimmunity in this mouse model. This new pathway could be targeted in a translational approach to modulate the capacity of T cells to differentiate in Tregs during autoimmune disease. Disclosure of Interest: F. Renoux Grant/research support from: Swisslife, M. Stellato: None declared, D. Impellizzieri: None declared, A. Vogetseder: None declared, R. Huang Employee of: Sanofi-Genzyme, A. Subramaniam Employee of: Sanofi-Genzyme, C. Dees: None declared, J. Distler Shareholder of: 4D Science, Grant/research support from: Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB, G. Kania: None declared, O. Boyman: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha